Can a Smartphone Application Be Used to Measure Practice Driving Behavior During the Learner Permit Period? A Step Toward Performance-Based Licensing - Johnathon P. Ehsani, PhD; Rebecca A. Weast, PhD; Theresa J. Chirles, PhD; Andrew Hellinger, BA; Gayane Yenokyan, PhD; Yifan Zhang, MS (Elsevier, 2023)
Introduction: Supervised practice during the learner stage of graduated driver licensing is required in all U.S. states and some international jurisdictions. Several U.S. states require driving hours to be recorded in a paper logbook, making it susceptible to errors or falsification. A smartphone app that operates as an electronic logbook could serve as an alternative. The purpose of this study was to measure the impact of the logbook format (i.e., paper versus electronic) on self-reported driving behavior. Design: Parent‒teen dyads were enrolled and assigned to electronic (n=147) and paper (n=131) logbook groups using a block design. Setting/Participants: This study was conducted in Maryland. Data were collected for 6 continuous months while teenagers held a learner permit between January 2020 and December 2021. Intervention: Electronic logbook to measure practice driving. Outcome measure: Self-reported driving between the electronic and paper logbook groups. For those using electronic logbooks, an agreement between self-reported trips and electronic logbook trips and perceptions of using an electronic logbook to measure driving. Results: There were no statistically significant differences in any measures of self-reported practice driving by logbook type (electronic versus paper). Agreement between self-reported and electronic logbook‒recorded trips ranged between 68.6% and 79.0% (allowing a difference of 2 trips per week). User satisfaction with the electronic logbook was high, with 93.0% of teenagers and 91.9% of parents stating that they would recommend the app to a friend. Conclusions: An electronic logbook is a viable approach to measuring practice driving. Eventually, it could become part of a system where practice requirements are verified, allowing states to move toward performance-based graduated driver licensing.